Technical evaluation of a Real-time polymerase chain reaction (PCR) assay for the detection of Bartonella spp for diagnostic purposes - Booley, Ghowa (Department of Clinical Laboratory Sciences, 2022)
Infective endocarditis (IE) is a rare disease affecting heart tissues. The laboratory diagnosis of culture-negative endocarditis is complicated, and largely based on the combination of nucleic acid detection methods and serological investigation. There is a paucity of published data on microbes causing culture-negative endocarditis, but a recent report indicated that the bacterium Bartonella was the commonest cause of culture-negative endocarditis at a tertiary care facility in Cape Town, South Africa. This laboratory-based, non-clinical pilot study, evaluated the utility of a previously published real-time PCR assay for detecting Bartonella spp. on cats. This will be the first time this target will be evaluated in a real-time PCR assay to detect Bartonella spp. in human samples. For this study, we constructed a plasmid vector containing an insert of 83bp, derived from the Bartonella nuoG gene. In this non-clinical, laboratory evaluation, we used one laboratory sample to amplify the nuoG bacterial DNA fragment and cloned it into a plasmid vector. Using this plasmid in a technical validation, we demonstrated that the previously described assay could detect nuoG when using the LightCycler 480 Probes Master Mix. The results indicated that the assay reliably detected as little as 1000 copies of the target DNA, and infrequently also detected 10-100 copies of the target. The study showed no amplification using some commonly encountered organisms found in our clinical setting, thus indicating 100% specificity for Bartonella. We demonstrated that a plasmid construct containing an internal fragment from the nuoG gene successfully detected the target using a real-time PCR assay. Future testing should include further optimisation to improve reaction efficiency of the assay with spiked diagnostic samples, including peripheral blood, and DNA extracted from heart valve samples. The utility of the RT-PCR for diagnostic purposes should be evaluated by comparing assay turnaround time, sensitivity, and specificity of this assay versus the conventional PCR and Sanger sequencing currently in use to detect Bartonella spp. in heart valves. We concluded that the assay exhibited strong potential for use as a diagnostic PCR using the constructed plasmid, but that further optimization to improve PCR efficiency, and work to determine the clinical sensitivity and specificity are needed before the assay can be applied to blood samples.